Agri-sense : an IOT - based horticulture monitoring system for rice agriculture. - Laguitao,GYrhyk Val S.Lirag, Justine Mark T. Lor, Claire Anne L. Rasing, Meiji Denzel Brianne A. Torres, John Michael Vincent P. 4 0 16; 5
ABSTRACT: STATEMENT OF THE PROBLEM: The researchers want to resolve and improve the Monitoring issues, Lack of strategic approach to irrigation practices, Varying levels of land moisture, and Unpredictable weather conditions. RESEARCH METHODOLOGY: The researchers use quantitative design which involves using numerical data to quantify soil moisture levels at different locations within the field. SUMMARY OF FINDINGS: The system can be utilized and can be properly used by the farmers and the owners approved can also monitor the rice field through the mobile application. CONCLUSION: In summary, the researchers were able to develop an IoT smart horticulture monitoring device, and successfully integrated a microcontroller suitable for the sensors and efficiency of the system. RECOMMENDATION: The researchers recommended to have an extra layer of security, consider using LoRa instead of Wi-Fi wide coverage for better data monitoring, have a better enclosure to accommodate climate changes, have an SMS notification incase of the Wi-Fi has no signal, consider testing on two separate rice field with different environment, use the point to multipoint for the data monitoring to be easily accessible by the users.
Undergraduate Thesis : (Bachelor of Science in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2